PEMANFAATAN SERBUK GERGAJI KAYU AKASIA (Acacia mangium Willd) SEBAGAI BAHAN BAKU ARANG AKTIF UNTUK MENINGKATKAN KUALITAS AIR BERSIH - , PRIHONO HADI; , Dr. Ir. J. P. Gentur Sutapa, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Acacia sawdust (AS) waste wich was resulted as by product from sawmilling process is quite abundant and have not been used optimally. One of efforts to reduce the waste volume is by using AS waste as activated charcoal raw material. Manufacturing of AS activated charcoal with varied combination treatment was used to produce a qualified AS activated charcoal for improving water quality. This research aims to determine the effect of the interaction between carbonization time, activation temperature and activation time to the quality and chemical structure of AS activated charcoal. Activated charcoal with highest quality was applied to improve water quality. AS wich was obtained from wood sawmill industry in Pelaihari, South Kalimantan province, was carbonized at 400Â°C for 3, 4 and 5 hours. The activation process was thermal activation at 700, 800 and 900Â°C with a variation of the activation time at 30, 60, and 90 minutes. Characteristics and quality of AS activated charcoal were examined included